Mário de Andrade’s Journey to the Amazon Between Roots and Routes - Botelho, André (Revista do Instituto de Estudos Brasileiros, 2013)
The article proposes a reading on the Amazon trip by Mário de Andrade, O turista aprendiz, valuing contingencies and ambiguities in the modeling of the narrative and the Narrator-traveler. Therefore, refuses to assimilate beforehand the Amazon travelogue to travel literature in general or even the idea of ethnographic trip so characteristic of the author’s other trip report, the one to Northeast. A quick comparison with the writings of Euclides da Cunha allows to discuss cultural translation and Intertextuality, and ressignification of the mandatory subjects on the Amazon travelogues and to get us a little closer to the sense of Mário de Andrade’s ideas, never free of ambiguities which precisely owe his strength, reach and contemporary interest.